Matrix representational method for identifying prominent features of architectural design process - Fahimeh Zaeri, 1979-; Khairul Anwar Mohamed Khaidzir, supervisor; Fakulti Alam Bina (2012)
Thesis (Sarjana Senibina) - Universiti Teknologi Malaysia, 2012